Strategies to support the mental health and well-being of health and care workforce: a rapid review of reviews - Frias, Cindy E.; Samarasinghe, Nimesh; Cuzco, Cecilia; Koorankot, Jaseem; de Juan, Andrés; Ali Rudwan, Husameldin Mohamed; Rahim, Hanan F. Abdul; Zabalegui, Adela; Tulley, Iain; Al-Harahsheh, Sanaa T.; Al-Homaiddi, Mona Shaheen S. T.; Fendt-Newlin, Meredith; et al. (Frontiers in Medicine, 2025)
BackgroundCountries globally face challenges in educating, employing and retaining their health and care workforce, largely due to underinvestment in health systems. Health and care workforce report significantly greater levels of job-related burnout and mental health problems, which in turn are associated with poorer patient outcomes, increased medical errors, diminished quality and safety, decreased patient satisfaction, and reduced healthcare efficiency.ObjectiveWe conducted a rapid review of systematic reviews to evaluate the mental health and well-being of health and care workers since the onset of the COVID-19 pandemic and to identify interventions available at organizational and individual levels.MethodsPubMed and Epistemonikos were searched for systematic reviews published between May 2022 and February 2024. The inclusion criteria were systematic reviews written in English with quantitative design, with or without meta-analysis.ResultsFifty articles met the criteria for inclusion in the analysis. Overall, there has not been a significant change in the prevalence of depression and anxiety among health and care workforce since 2022, suggesting the impact of the COVID-19 pandemic on workers’ mental health and well-being was not specific to their experience working during the pandemic. Sixteen studies reported two types of mental health and well-being interventions: individual-level interventions and organizational-level interventions with specific impact on mental health and work environment variables. No specific policy interventions were found. However, some studies suggested policy interventions to improve the mental health and well-being of the health and care workforce.DiscussionOur analysis highlighted the need for systemic changes to protect the mental health and well-being of the health and care workforce in the post-COVID-19 era. Despite the wealth of evidence on mental health problems and on effective interventions, there remains a notable gap in systemic implementation and organizational accountability. The call to action for a paradigm shift must be embraced and we must strive to build resilient healthcare systems and invest in active support and sustain them, incorporating structural, non-structural and functional aspects of organizational resilience.